X-RAY MAMMOGRAPHY IN DIFFERENCES BETWEEN MASTITIS AND INFLAMMATORY BREAST CANCER - Fayzullaeva Madina Bakhshullo kizi; Boysariyeva Marjona Ravshan kizi; Norboeva Munisa Orif kizi; Nazrullayeva Nodira Najmiddin kizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:  Breast  cancer  is  more  common  in  women  over  the  age  of  45. Infiltrative breast cancer accounts for 1-5% of all breast cancers. This article reviews the  diagnosis  of  infiltrative  breast  cancer,  mammography  and  sonoscopy,  and  the differential diagnosis with mastitis.